2019
DOI: 10.1007/s11104-019-04229-0
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the nutritional quality of crop plants under a changing climate: importance and strategies

Abstract: Background Global climate is changing more rapidly than ever, threatening plant growth and productivity while exerting considerable direct and indirect effects on the quality and quantity of plant nutrients. Scope This review focuses on the global impact of climate change on the nutritional value of plant foods. It showcases the existing evidence linking the effects of climate change factors on crop nutrition and the concentration of nutrients in edible plant parts. It focuses on the effect of elevated CO 2 (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 221 publications
(107 citation statements)
references
References 220 publications
(298 reference statements)
3
102
1
1
Order By: Relevance
“…Our results are consistent with previous findings where the application of CMP did not increase Zn concentrations in the plant organs or it decreased it slightly (Zhou et al, 2017). Soares et al (2019) reported that broad bean plants accumulated increasing levels of Zn in the treatments with low or moderate CMP addition to the soils; in contrast, its content decreased significantly in the different organs of the plants with higher soil CMP additions. The authors postulated that this phenomenon might be caused by the lower available Zn content into the soil due to CMP sequestration.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous findings where the application of CMP did not increase Zn concentrations in the plant organs or it decreased it slightly (Zhou et al, 2017). Soares et al (2019) reported that broad bean plants accumulated increasing levels of Zn in the treatments with low or moderate CMP addition to the soils; in contrast, its content decreased significantly in the different organs of the plants with higher soil CMP additions. The authors postulated that this phenomenon might be caused by the lower available Zn content into the soil due to CMP sequestration.…”
Section: Discussionsupporting
confidence: 93%
“…Agriculture and climate change are interrelated to each other, and the global climate is changing more rapidly than ever before [1]. Water limitation is a major constraint in global crop growth, development, and production, and climate change is the leading cause of it, thus worsening this situation extravagantly with adverse effects on agriculture in most regions of the world [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Plant-associated microorganisms produce substances such as phytohormones and antibiotics which support plant growth and provide protection against pathogens (Plant Growth Promoting Bacteria, PGPB) [4,8,9]. This property can help improve crop production-one of today's most important issues due to rising human population and the shortage in resources [10]. In addition, these microorganisms can help plants to survive stress conditions, e.g.…”
Section: Introductionmentioning
confidence: 99%